PERANCANGAN SISTEM INFORMASI TRAINING PADA PUSAT PENDIDIKAN DAN PELATIHAN PT SUMALINDO LESTARI JAYA - Sugiyono, Sugiyono (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
PT Sumalindo Lestari Jaya, Tbk. is a company engaged in the production of plywood which operates in the East Kalimantan region and employs thousands of employees in it. In order to maintain the quality of its products, the company is highly committed to improving skills and developing its human resources. The management of HR development activities in this company is handled by the Pusdiklat division. The management of education and training, which is currently still manual, raises its own problems in terms of planning and scheduling of training, training participant selection processes, reporting mechanisms, an untidy documentation system to the implementation of activity output evaluations, which is why researchers are interested in examining this issue. The method used is Research and Development in the form of software design that produces Information Systems as a tool in managing training.